Lithium iron phosphate positive electrode material, preparation method thereof, lithium ion battery and electrical equipment

CN122930903APending Publication Date: 2026-10-16GUIZHOU CNGR XINGYANG ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610966123.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,目前行业内对纳米颗粒的尺寸分布及其比例缺乏明确的、可量化的优化标准

Benefits of technology

本发明提供的磷酸铁锂正极材料通过精确控制纳米颗粒数量占比,使得颗粒中颗粒尺寸≤100nm的颗粒数量占比≥80%,这一分布特征极大缩短了锂离子在固相中的扩散距离(由微米级降至纳米级),同时大幅增加了电极/电解液接触面积,有效降低了电化学极化和浓差极化。在充放电过程中,电能转化为化学能的损耗显著减少,能量效率(主要表现为1C放电容量及1C放电3.2V平台占比)处于优异水平。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930903A_ABST
    Figure CN122930903A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lithium ion positive electrode materials, and discloses a lithium iron phosphate positive electrode material, a preparation method thereof, a lithium ion battery and an electrical equipment. In the particles of the lithium iron phosphate positive electrode material, the number proportion of particles with a particle size of less than or equal to 100 nm is greater than or equal to 80%. The lithium iron phosphate positive electrode material provided by the application can realize the shortest lithium ion diffusion path, the maximum exposed active site and the most closely and uniformly contacted conductive network; the specific particle size distribution range ensures that most of the particles in the material are in the high-efficiency reaction size interval, thereby significantly reducing electrochemical polarization, and greatly improving the diffusion rate of lithium ions in the solid phase and the interface charge transfer efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion cathode material technology, specifically to lithium iron phosphate cathode materials and their preparation methods, lithium-ion batteries, and electrical equipment. Background Technology

[0002] Lithium iron phosphate, as a cathode material for lithium-ion batteries, has advantages such as structural stability, long cycle life, high thermal safety, environmental friendliness, and low cost, and has been widely used in electric vehicles, energy storage systems, and portable electronic devices.

[0003] However, lithium iron phosphate inherently has low electronic conductivity (approximately 10). -9 S / cm), and the lithium-ion diffusion coefficient is small (approximately 10). -14 ~10 -12 The capacity decays rapidly under high-rate charge and discharge conditions (cm² / s), resulting in a significant decrease in energy efficiency. This has become a key technical bottleneck restricting its further development in high-power applications.

[0004] To overcome the aforementioned shortcomings, existing technologies mainly employ modification strategies such as carbon coating, ion doping, and particle nanostructuring. Among these, particle nanostructuring has been proven to be one of the most direct and effective methods for shortening the lithium-ion solid-phase diffusion path, increasing the electrode / electrolyte contact area, and improving reaction kinetics. However, the industry currently lacks clear and quantifiable optimization standards for the size distribution and proportion of nanoparticles. Summary of the Invention

[0005] The purpose of this invention is to provide a lithium iron phosphate cathode material and its preparation method, a lithium-ion battery, and electrical equipment, aiming to solve at least one of the above-mentioned technical problems in the prior art.

[0006] To achieve the above objectives, a first aspect of the present invention provides a lithium iron phosphate cathode material, wherein the number of particles with a particle size ≤100nm accounts for ≥80% of the particles in the lithium iron phosphate cathode material.

[0007] According to a preferred embodiment, in the lithium iron phosphate cathode material particles, the proportion of particles with a particle size ≤50nm is ≥50%.

[0008] Optionally, in the lithium iron phosphate cathode material particles, the proportion of particles with a particle size ≤100nm is ≥90%.

[0009] Optionally, the chemical formula of the lithium iron phosphate cathode material is Li a Fe b M c P dO4, wherein 0.9≤a≤1.05, 1.0≤a / b<1.12, 0.95≤a / d≤1.05, 0.9≤b+c≤1.1, and M is selected from at least one of Ru, Rh, Pd, Mg, Nb, V, Ti, Mo, Al, Mn, and Os.

[0010] Optionally, in the lithium iron phosphate cathode material particles, the proportion of particles with a size of 1000-3000 nm is 2-3%.

[0011] Optionally, the average size of the particles is 40-80 nm.

[0012] According to another preferred embodiment, the lithium iron phosphate cathode material satisfies at least one of the following conditions: (1) The sphericity of the lithium iron phosphate cathode material is ≥78%; (2) The particle size D50 of the lithium iron phosphate cathode material is 0.7-1.1 μm; (3) The compaction density of the lithium iron phosphate cathode material is 2.50-2.65 g / cm³. 3 ; (4) The particle size distribution of the lithium iron phosphate cathode material is Span=(D90-D10) / D50, which is 20-40.

[0013] A second aspect of the present invention provides a method for preparing the lithium iron phosphate cathode material described in the first aspect, the method comprising: The lithium source, iron source, phosphorus source and carbon source I are mixed and then subjected to sand milling I to obtain a slurry; The slurry is subjected to drying treatment I and sintering treatment I in sequence to obtain the first sintered product; The first sintered product and carbon source II are sequentially subjected to sand milling II, drying II, and sintering II to obtain the second sintered product; The second sintered product is pulverized to obtain the lithium iron phosphate cathode material.

[0014] According to a preferred embodiment, the method satisfies at least one of the following conditions: A. The carbon source I and the carbon source II are each independently selected from at least one of glucose, sucrose, citric acid, and polyethylene glycol; optionally, the amount of carbon source I and carbon source II added is each independently 2%-15% of the mass of the iron source; B. The slurry further contains a dispersant; optionally, the dispersant is selected from at least one of polyethylene glycol, polyvinylpyrrolidone, and hexadecyl dimethyl ammonium bromide; optionally, the amount of the dispersant added is 0.1%-5% of the mass of the iron source. C. The solid content of the slurry is 40wt%-50wt%; D. The molar ratio of lithium in the lithium source, iron in the iron source, and phosphorus in the phosphorus source is (0.95-1.05):(0.95-0.99):1; E. The sand milling process I is carried out in the presence of a first additive; optionally, the first additive is selected from at least one of hexadecyltrimethylammonium bromide, polyvinylpyrrolidone and sodium dodecyl sulfate. F. The conditions for the sand milling treatment I include: a rotation speed of 1000-2500 rpm and a time of 4-10 h; G. The drying process I includes spray drying I; optionally, the inlet air temperature of the spray drying I is 260-280℃ and the outlet air temperature is 90-110℃. H. The conditions for the sintering treatment I include: a temperature of 650~780℃ and a time of 2~5h; I. The sintering atmospheres of sintering treatment I and sintering treatment II each independently include at least one of nitrogen and argon.

[0015] According to a preferred embodiment, the method satisfies at least one of the following conditions: a. The mass ratio of the first sintered product to the carbon source II is 1:0.02~0.05; c. The conditions for the sand milling treatment II include: a rotation speed of 400-2500 rpm and a time of 2-6 hours; d. The drying process II includes spray drying II; optionally, the inlet air temperature of the spray drying II is 260-280℃ and the outlet air temperature is 90-110℃. e. The conditions for the sintering treatment II include: a temperature of 750~820℃ and a time of 5~10h; f. The particle size D50 of the slurry is 0.2-0.5 μm; g. The material after the sand milling treatment II includes large particles with a particle size D50 of 0.6-1.2μm and small particles with a particle size D50 of 0.2-0.4μm; based on the total mass of the material after the sand milling treatment II, the mass percentage of the large particles is 30-70wt%.

[0016] A third aspect of the present invention provides a lithium-ion battery comprising a lithium iron phosphate cathode material as described in the first aspect above or a lithium iron phosphate cathode material prepared by the preparation method described in the second aspect above.

[0017] A fourth aspect of the present invention provides an electrical device comprising a lithium-ion battery as described in the third aspect above.

[0018] Compared with the prior art, the technical solution provided by the present invention has at least the following advantages: The lithium iron phosphate cathode material provided by this invention achieves a precise control over the proportion of nanoparticles, resulting in ≥80% of the particles having a size ≤100nm. This distribution characteristic significantly shortens the diffusion distance of lithium ions in the solid phase (from the micrometer level to the nanometer level) and substantially increases the electrode / electrolyte contact area, effectively reducing electrochemical polarization and concentration polarization. During charging and discharging, the loss of electrical energy converted into chemical energy is significantly reduced, and the energy efficiency (mainly reflected in the 1C discharge capacity and the proportion of the 3.2V 1C discharge plateau) is at an excellent level.

[0019] The method for preparing lithium iron phosphate cathode material provided by this invention can precisely achieve a specific nanoparticle size distribution by controlling the initial particle size and particle growth during the grinding and sintering process, without the need for complex classification equipment. It offers a wide process window, good repeatability, is easy to scale up industrially, and has controllable costs.

[0020] When the lithium iron phosphate cathode material provided by this invention is applied to lithium-ion batteries, the resulting lithium-ion batteries have high capacity. Attached Figure Description

[0021] Figure 1 Here is a SEM image of the lithium iron phosphate cathode material prepared in Example 2 of this invention; Figure 2 This is a SEM image of the lithium iron phosphate cathode material prepared in Comparative Example 2 of this invention. Detailed Implementation

[0022] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0023] It should be noted that the "size" of a single particle in this invention is measured by selecting the maximum distance between two points on the outer contour edge of the particle.

[0024] In this invention, "solid content" refers to the percentage of the mass of non-volatile solid components in the slurry relative to the total mass of the slurry.

[0025] In this invention, the particle size distribution was obtained by electron microscopy (SEM, JEOL JEM-2100F) and particle identification and statistics of no less than 100 particles.

[0026] As mentioned above, the first aspect of the present invention provides a lithium iron phosphate cathode material in which the number of particles with a particle size ≤100nm accounts for ≥80%, for example, the number of particles with a particle size ≤100nm can be any value of 80%, 85%, 90%, 95% or ≥80%.

[0027] In this invention, by controlling the proportion of particles with a size ≤100nm in the lithium iron phosphate cathode material to be ≥80%, the lithium-ion diffusion path can be shortened, while the electrode / electrolyte contact area is significantly increased, effectively reducing electrochemical polarization and concentration polarization. During charging and discharging, the loss of electrical energy converted into chemical energy is significantly reduced, and the energy efficiency (mainly reflected in the 1C discharge capacity and the proportion of the 3.2V 1C discharge plateau) is at an excellent level.

[0028] In some embodiments, the number of particles with a particle size ≤100nm in the lithium iron phosphate cathode material accounts for ≥90%, for example, the number of particles with a particle size ≤100nm can be any value of 90%, 95%, 98% or ≥90%.

[0029] In some embodiments, the proportion of particles with a particle size ≤50nm in the lithium iron phosphate cathode material is ≥50%. For example, the proportion of particles with a particle size ≤50nm can be any value of 50%, 60%, 70%, 80%, 85%, 90%, 95% or ≥50%.

[0030] In some embodiments of the present invention, since ultra-small particles of 0-50 nm constitute the majority (≥50%), it ensures that almost all particles in the electrode are in a fast-response state; these particles can achieve almost "instantaneous" solid-phase lithium-ion diffusion (diffusion time is proportional to the square of the particle size). This makes it particularly suitable for fields requiring rapid charging and discharging, such as power tools, hybrid vehicles, and high-end drones.

[0031] According to a preferred embodiment, the chemical formula of the lithium iron phosphate cathode material is Li a Fe b M c P d O4, wherein 0.9≤a≤1.05, 1.0≤a / b<1.12, 0.95≤a / d≤1.05, 0.9≤b+c≤1.1, and M is selected from at least one of Ru, Rh, Pd, Mg, Nb, V, Ti, Mo, Al, Mn, and Os.

[0032] In some embodiments, the proportion of particles with a size of 1000-3000 nm in the lithium iron phosphate cathode material is 2-3%. For example, the proportion of particles with a size of 1000-3000 nm can be any value between 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, or 2-3%. In some embodiments of the present invention, the proportion of particles with a size of 1000-3000 nm in the lithium iron phosphate cathode material is within the above range, which can achieve a good gradation effect, so that the product has excellent electrochemical performance and high compaction density.

[0033] In some embodiments, the average size of the particles is 40-80 nm, for example, it can be any value between 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, or 40-80 nm. Although the particles in the lithium iron phosphate cathode material are small in size and have a large specific surface area, the present invention avoids the presence of too many ultrafine powders (such as <10 nm particles) and medium and large particles (>200 nm particles) through a narrow particle size distribution, thereby reducing stress concentration and structural damage caused by excessive agglomeration or large particles, and achieving a balance between high rate and long cycle life.

[0034] In some embodiments, the sphericity of the lithium iron phosphate cathode material is ≥78%, for example, the sphericity can be any value of 78%, 80%, 85%, 90%, 95%, 98%, 99%, or ≥78%. In some embodiments of the present invention, the particle morphology of the lithium iron phosphate cathode material is near-spherical or quasi-spherical, and the sphericity meets the above-mentioned range, so as to facilitate uniform particle stacking and the construction of conductive network.

[0035] In some embodiments, the particle size D50 of the lithium iron phosphate cathode material is 0.7-1.1 μm, for example, it can be any value between 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm or 0.7-1.1 μm.

[0036] In some embodiments, the compaction density of the lithium iron phosphate cathode material is 2.50-2.65 g / cm³. 3 For example, it can be 2.50 g / cm³. 3 2.55g / cm 3 2.60g / cm 3 2.65g / cm 3 Or 2.50-2.65 g / cm³ 3 Any value between.

[0037] In some embodiments, the particle size distribution of the lithium iron phosphate cathode material, Span = (D90 - D10) / D50, is 20-40. For example, Span can be any value between 20, 25, 30, 35, 40, or 20-40. In some embodiments of the present invention, the particle size distribution Span of the lithium iron phosphate cathode material is within the above-mentioned range, which can improve the compaction density of the cathode material and thereby improve the volumetric energy density of the corresponding lithium-ion battery.

[0038] As previously described, a second aspect of the present invention provides a method for preparing the lithium iron phosphate cathode material described in the first aspect, the method comprising: The lithium source, iron source, phosphorus source and carbon source I are mixed and then subjected to sand milling I to obtain a slurry; The slurry is subjected to drying treatment I and sintering treatment I in sequence to obtain the first sintered product; The first sintered product and carbon source II are sequentially subjected to sand milling II, drying II, and sintering II to obtain the second sintered product; The second sintered product is pulverized to obtain the lithium iron phosphate cathode material.

[0039] In some embodiments, the mixing operation is carried out in a mixing tank, under conditions including stirring for 30-120 minutes to ensure thorough and uniform mixing.

[0040] In some embodiments, carbon source I and carbon source II are each independently selected from at least one of glucose, sucrose, citric acid, and polyethylene glycol.

[0041] In some embodiments, the amount of carbon source I and carbon source II added is independently 2%-15% of the mass of the iron source, for example, the amount of carbon source I and carbon source II added is independently any value between 2%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15% or 2%-15% of the mass of the iron source.

[0042] In some embodiments, the slurry further contains a dispersant; optionally, the dispersant is selected from at least one of polyethylene glycol, polyvinylpyrrolidone, and hexadecyl dimethyl ammonium bromide.

[0043] In some embodiments, the amount of dispersant added is 0.1%-5% of the mass of the iron source, for example, the amount of dispersant added is any value between 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 2%, 3%, 4%, 5% or 0.1%-5% of the mass of the iron source.

[0044] In some embodiments, the slurry has a solid content of 40wt%-50wt%, for example, the solid content can be any value between 40wt%, 45wt%, 50wt%, or 40wt%-50wt%.

[0045] In some embodiments, the particle size D50 of the slurry is 0.2-0.5 μm, for example, it can be any value between 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm or 0.2-0.5 μm.

[0046] In some embodiments, the molar ratio of lithium in the lithium source, iron in the iron source, and phosphorus in the phosphorus source is (0.95–1.05):(0.95–0.99):1, for example, it can be any value between 0.95:0.95:1, 1:0.95:1, 1.05:0.95:1, 0.95:0.99:1, 1:0.99:1, 1.05:0.99:1, or (0.95–1.05):(0.95–0.99):1.

[0047] In some embodiments, the milling process I is carried out in the presence of a first additive; optionally, the first additive is selected from at least one of hexadecyltrimethylammonium bromide, polyvinylpyrrolidone, and sodium dodecyl sulfate.

[0048] In some embodiments, the conditions for the sand milling process I include: a rotational speed of 1000-2500 rpm, for example, any value between 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm, or 1000-2500 rpm; and a time of 4-10 h, for example, any value between 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, or 4-10 h.

[0049] In some embodiments, the drying process I includes spray drying I; optionally, the inlet air temperature of the spray drying I is 260-280°C, for example, it can be any value between 260°C, 265°C, 270°C, 280°C or 260-280°C; the outlet air temperature is 90-110°C, for example, it can be any value between 90°C, 95°C, 100°C, 110°C or 90-110°C.

[0050] In some embodiments, the conditions for the sintering treatment I include: a temperature of 650~780℃, for example, any value between 650℃, 680℃, 700℃, 750℃, 780℃ or 650~780℃; and a time of 2~5h, for example, any value between 2h, 3h, 4h, 5h or 2~5h.

[0051] In some embodiments, the sintering atmosphere of sintering treatment I and sintering treatment II each independently includes at least one of nitrogen and argon.

[0052] In some embodiments, the mass ratio of the first sintered product to the carbon source II is 1:0.02 to 0.05, for example, it can be any value between 1:0.02, 1:0.03, 1:0.04, 1:0.05 or 1:0.02 to 0.05.

[0053] In some embodiments, the conditions for the sand milling treatment II include: a rotational speed of 400-2500 rpm, for example, any value between 400 rpm, 600 rpm, 800 rpm, 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm, or 400-2500 rpm; and a time of 2-6 hours, for example, any value between 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, or 2-6 hours.

[0054] In some embodiments, the material after the sand milling treatment II includes large particles with a particle size D50 of 0.6-1.2 μm and small particles with a particle size D50 of 0.2-0.4 μm; based on the total mass of the material after the sand milling treatment II, the mass percentage of the large particles is 30-70 wt%, for example, it can be any value between 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, or 30-70 wt%.

[0055] In order to better control the particle size D50 of the material after the sand milling treatment II to meet the above requirements, in some embodiments, the first sintered product can be subjected to the sand milling treatment II separately, and the time of each sand milling treatment II can be controlled to obtain large particles and small particles in the above particle size D50 range respectively.

[0056] In some embodiments, the drying process II includes spray drying II; optionally, the inlet air temperature of the spray drying II is 260-280°C, for example, it can be any value between 260°C, 265°C, 270°C, 280°C or 260-280°C; the outlet air temperature is 90-110°C, for example, it can be any value between 90°C, 95°C, 100°C, 110°C or 90-110°C.

[0057] In some embodiments, the conditions for the sintering treatment II include: a temperature of 750~820°C, for example, any value between 750°C, 780°C, 800°C, 820°C or 750~820°C; and a time of 5~10h, for example, any value between 5h, 6h, 7h, 8h, 9h, 10h or 5~10h.

[0058] As previously stated, a third aspect of the present invention provides a lithium-ion battery comprising the lithium iron phosphate cathode material as described in the first aspect or the lithium iron phosphate cathode material prepared by the preparation method described in the second aspect.

[0059] As previously described, a fourth aspect of the present invention provides an electrical device including a lithium-ion battery as described in the third aspect above.

[0060] The present invention will be described in detail below through examples. Unless otherwise specified, the instruments, reagents, and materials involved in the following examples are all conventional instruments, reagents, and materials, which can be obtained through legitimate commercial channels. Unless otherwise stated, all reagents used are commercially available analytical grade products.

[0061] Example 1 This embodiment illustrates the preparation of lithium iron phosphate cathode material according to a method including the following steps: (1) Dissolve lithium source (specifically lithium carbonate), iron source (specifically iron oxide), and phosphorus source (specifically ammonium dihydrogen phosphate) in deionized water at a molar ratio of Li:Fe:P = 1.01:0.97:1, add carbon source I (specifically glucose, the amount added is 13% of the mass of iron oxide) and dispersant (polyethylene glycol, the amount added is 2% of the mass of iron oxide), and ultrasonically disperse to form a uniform mixture; (2) Sand milling treatment I: The mixture and the first additive (hexadecyltrimethylammonium bromide, the amount added is 0.1% of the mass of iron oxide) are transferred into a sand mill, water is added, and sand milling treatment I is carried out (speed is 1300 rpm, time is 5h). The amount of water added is controlled to obtain a slurry with a solid content of 40wt% (particle size D50 is 0.45μm). (3) The slurry is dried (the slurry after sand milling is spray dried using a spray dryer with inlet and outlet air temperatures of 270 / 100℃ respectively) to obtain the spray-dried material; (4) Sintering treatment I: Under a nitrogen atmosphere, the spray-dried material is transferred to a box furnace for sintering treatment I (temperature is 650℃, time is 3h). After sintering, the material is passed through a 50-mesh sieve (Chinese standard sieve, the undersize material is taken) to obtain the first sintered product. (5) Sand milling treatment II: Take the first sintered product, add 5 wt% (based on the first sintered product) of carbon source II (specifically sucrose), and perform sand milling treatment II in a sand mill. Control the grinding time of grinding treatment II, test the particle size of the material every 20 minutes of grinding. When the particle size of the material reaches the target large particle D50, take out 50wt% of the total material; continue grinding the remaining 50wt% of the material until the target small particle D50 is reached; mix the large and small particles so that the material after sand milling treatment II includes large particles with D50 of 1.2μm (based on the total mass of the material after sand milling treatment II, the mass ratio of large particles is 50wt%) and small particles with D50 of 0.4μm; The material after sand milling treatment II is subjected to drying treatment II (the sand-milled slurry is spray-dried using a spray dryer with inlet and outlet air temperatures of 270 / 100℃) to obtain the spray-dried material. (6) Sintering treatment II: Under a nitrogen atmosphere, the spray-dried material obtained in step (5) is subjected to sintering treatment II (temperature 760℃, time 7h). (7) Depolymerization treatment: The product obtained in step (6) is subjected to airflow / mechanical pulverization treatment to obtain lithium iron phosphate cathode material.

[0062] The average particle size of the lithium iron phosphate cathode material prepared in this embodiment was measured to be 55.79 nm using SEM images.

[0063] Example 2 This embodiment uses a method similar to that of Embodiment 1, except that: In step (5), by controlling the grinding time of grinding treatment II, the material after sand milling treatment II includes large particles with a D50 of 1.2 μm (based on the total mass of the material after sand milling treatment II, the mass percentage of large particles is 50 wt%) and small particles with a D50 of 0.2 μm. All parts not listed are the same as in Example 1.

[0064] Example 3 This embodiment uses a method similar to that of Embodiment 1, except that: In step (5), by controlling the grinding time of grinding treatment II, the material after sand milling treatment II includes large particles with a D50 of 0.7 μm (based on the total mass of the material after sand milling treatment II, the mass percentage of large particles is 60 wt%) and small particles with a D50 of 0.2 μm. All parts not listed are the same as in Example 1.

[0065] Example 4 This embodiment uses a method similar to that of Embodiment 1, except that: In step (5), by controlling the grinding time of grinding treatment II, the material after sand milling treatment II includes large particles with a D50 of 0.6 μm (based on the total mass of the material after sand milling treatment II, the mass percentage of large particles is 60 wt%) and small particles with a D50 of 0.4 μm. All parts not listed are the same as in Example 1.

[0066] Comparative Example 1 This comparative example was conducted using a method similar to that of Example 1, except that: In step (5), by controlling the grinding time of grinding treatment II, the material after sand milling treatment II includes large particles with a D50 of 1.6 μm (based on the total mass of the material after sand milling treatment II, the mass ratio of large particles is 50 wt%) and small particles with a D50 of 0.2 μm. All parts not listed are the same as in Example 1.

[0067] Comparative Example 2 This comparative example was conducted using a method similar to that of Example 1, except that: In step (5), by controlling the grinding time of grinding treatment II, the material after sand milling treatment II includes large particles with a D50 of 0.5 μm (based on the total mass of the material after sand milling treatment II, the mass ratio of large particles is 50 wt%) and small particles with a D50 of 0.2 μm. All parts not listed are the same as in Example 1.

[0068] The particle number distribution of the lithium iron phosphate cathode material prepared in this comparative example, as measured by SEM images, satisfies the following: There are a large number of ultrafine powders <10nm (accounting for about 35%), but at the same time, a large number of hard agglomerates >200nm are formed (accounting for about 25%). The number of 0-50nm particles accounts for 52.6%, but the number of 0-100nm particles accounts for only 64.41%, indicating severe agglomeration and poor dispersibility. The number of 1000-3000nm particles accounts for 4.59%.

[0069] Comparative Example 3 This comparative example uses a commercially available nano-lithium iron phosphate sample (a commercially available product), with an average particle size of approximately 346.8 nm, containing a considerable proportion of large particles (>200 nm) and ultrafine powder.

[0070] Comparative Example 4 This comparative example was conducted using a method similar to that of Example 1, except that: In step (5), after carbon source II is added, the mixture is stirred with a mechanical stirrer at 1000 rpm for 10 min.

[0071] The particle number distribution of the lithium iron phosphate cathode material prepared in this comparative example, as measured by SEM images, satisfies the following: The number of particles in the 0-50 nm range was 41.3%, and the number of particles in the 0-100 nm range was 71.6%, with an average particle size of 269.12 nm. The carbon source was unevenly distributed on the particle surface, and the particles in the areas lacking carbon coating agglomerated and grew during sintering, forming large particles of 1000-3000 nm (accounting for 4.68%).

[0072] Test Example 1 The cathode materials prepared in the aforementioned examples were subjected to physicochemical data testing, and the test results are shown in Table 1; specifically: 1. Particle size D50 and particle size distribution Span-(D90-D10) / D50 were tested using a Malvern 3000 laser particle size analyzer, referring to standard GB / T 19077-2016; 2. Compaction density conditions: The compaction density was tested using a Sansi Zongheng UIM 7305 compaction density tester. The test method is as follows: Weigh 1g of the material to be tested and place it in a clean mold. The radius of the hole in the mold is 13mm. Then place the mold on the pressure plate of the equipment and select a test pressure of 3T for testing. 3. The sphericity test method is as follows: The Avizo sphericity analysis software is used to intelligently identify all lithium iron phosphate particles in the SEM image. The sphericity is calculated using the formula: Sphericity = Area of ​​the circumscribed circle corresponding to the shortest diameter / Area of ​​the circumscribed circle corresponding to the longest diameter × 100%. The closer the shape is to a circle, the closer it is to 100%. Several SEM images (e.g., 5 images) can be used to calculate the sphericity, and then the average value is taken. All sphericity measurements in this paper were obtained using this method. 4. The percentage of lithium iron phosphate cathode material particles was obtained by electron microscopy (SEM, JEOL JEM-2100F) and particle identification and statistics of no less than 100 particles.

[0073] Table 1. Structural parameters of the cathode materials prepared in the examples and comparative examples.

[0074] Test Example 2 The present invention provides, by way of example, SEM characterization of the aforementioned Embodiment 2 and Comparative Example 2, as follows: Figure 1 , Figure 2 As shown: The results showed that the particles in Example 2 were small, with the particle size concentrated in the range of 0-100nm, while some large particles above 1000nm provided a certain gradation effect; the particles in Comparative Example 2 were larger, mainly concentrated above 200nm, with poorer particle dispersion and lower sphericity.

[0075] Test Example 3 Preparation of lithium-ion batteries: (1) The above-mentioned lithium-ion battery positive electrode material, conductive carbon black and binder PVDF (polyvinylidene fluoride) are mixed into a slurry in a ratio of 8:1:1 and uniformly coated on an aluminum foil with a length and width of 2cm×1cm to form a positive electrode sheet; (2) In a vacuum glove box, the battery case, positive electrode, negative electrode (lithium metal sheet), separator (Celgard2400), spring sheet, gasket, and electrolyte (1 mol / L LiPF6 dissolved in EC / DMC / EMC with a volume ratio of 1:1:1) are assembled into a CR2032 coin cell.

[0076] The electrochemical performance of the prepared lithium-ion batteries was tested using the Blue Electric CT3002A testing system, as detailed below: ① Capacity test: The prepared coin cells were subjected to a complete “charge-rest-discharge” process at approximately 25°C at rates of 0.1C, 1C, and 5C. ② Cycle performance test: The prepared button cell battery was subjected to 3 charge-discharge cycles at approximately 25°C and within a voltage range of 2.0-3.75V. Wherein, 1C = 160mAh / g (nominal capacity); 1C discharge 3.2V plateau retention rate = (3.75 - 3.2V discharge capacity) / (3.75 - 2.0V discharge capacity) × 100%; Capacity retention rate after 500 cycles at 1C = (Discharge capacity after 500 cycles) / (Discharge capacity after the first cycle) × 100%; The test results are shown in Table 2: Table 2

[0077] The results above demonstrate that the lithium iron phosphate cathode material provided by this invention, through precise control of the proportion of nanoparticles, achieves a particle size of ≤100nm of ≥80%. This distribution characteristic significantly shortens the diffusion distance of lithium ions in the solid phase and substantially increases the electrode / electrolyte contact area, effectively reducing electrochemical polarization and concentration polarization. During charging and discharging, the loss of electrical energy converted into chemical energy is significantly reduced, resulting in excellent energy efficiency. The 1C discharge capacity is ≥147mAh / g, and the 1C discharge 3.2V plateau retention rate is ≥95%.

[0078] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A lithium iron phosphate cathode material, characterized in that, In the lithium iron phosphate cathode material, particles with a size ≤100nm account for ≥80% of the total number of particles.

2. The lithium iron phosphate cathode material according to claim 1, characterized in that, In the lithium iron phosphate cathode material particles, the proportion of particles with a size ≤50nm is ≥50%; And / or, in the particles of the lithium iron phosphate cathode material, the proportion of particles with a particle size ≤100nm is ≥90%.

3. The lithium iron phosphate cathode material according to claim 1, characterized in that, The chemical formula of the lithium iron phosphate cathode material is Li a Fe b M c P d O4, wherein 0.9≤a≤1.05, 1.0≤a / b<1.12, 0.95≤a / d≤1.05, 0.9≤b+c≤1.1, and M is selected from at least one of Ru, Rh, Pd, Mg, Nb, V, Ti, Mo, Al, Mn, and Os.

4. The lithium iron phosphate cathode material according to any one of claims 1-3, characterized in that, In the lithium iron phosphate cathode material particles, the proportion of particles with a size of 1000-3000 nm is 2-3%; And / or, the average size of the particles is 40-80 nm.

5. The lithium iron phosphate cathode material according to any one of claims 1-3, characterized in that, The lithium iron phosphate cathode material satisfies at least one of the following conditions: (1) The sphericity of the lithium iron phosphate cathode material is ≥78%; (2) The particle size D50 of the lithium iron phosphate cathode material is 0.7-1.1 μm; (3) The compaction density of the lithium iron phosphate cathode material is 2.50-2.65 g / cm³. 3 ; (4) The particle size distribution of the lithium iron phosphate cathode material is Span=(D90-D10) / D50, which is 20-40.

6. A method for preparing the lithium iron phosphate cathode material according to any one of claims 1-5, characterized in that, The method includes: The lithium source, iron source, phosphorus source and carbon source I are mixed and then subjected to sand milling I to obtain a slurry; The slurry is subjected to drying treatment I and sintering treatment I in sequence to obtain the first sintered product; The first sintered product and carbon source II are sequentially subjected to sand milling II, drying II, and sintering II to obtain the second sintered product; The second sintered product is pulverized to obtain the lithium iron phosphate cathode material.

7. The method according to claim 6, characterized in that, The method satisfies at least one of the following conditions: A. The carbon source I and the carbon source II are each independently selected from at least one of glucose, sucrose, citric acid, and polyethylene glycol; optionally, the amount of carbon source I and carbon source II added is each independently 2%-15% of the mass of the iron source; B. The slurry further contains a dispersant; optionally, the dispersant is selected from at least one of polyethylene glycol, polyvinylpyrrolidone, and hexadecyl dimethyl ammonium bromide; optionally, the amount of the dispersant added is 0.1%-5% of the mass of the iron source. C. The solid content of the slurry is 40wt%-50wt%; D. The molar ratio of lithium in the lithium source, iron in the iron source, and phosphorus in the phosphorus source is (0.95-1.05):(0.95-0.99):1; E. The sand milling process I is carried out in the presence of the first additive; Optionally, the first additive is selected from at least one of hexadecyltrimethylammonium bromide, polyvinylpyrrolidone, and sodium dodecyl sulfate; F. The conditions for the sand milling treatment I include: a rotation speed of 1000-2500 rpm and a time of 4-10 h; G. The drying process I includes spray drying I; optionally, the inlet air temperature of the spray drying I is 260-280℃ and the outlet air temperature is 90-110℃. H. The conditions for the sintering treatment I include: a temperature of 650~780℃ and a time of 2~5h; I. The sintering atmospheres of sintering treatment I and sintering treatment II each independently include at least one of nitrogen and argon.

8. The method according to claim 6 or 7, characterized in that, The method satisfies at least one of the following conditions: a. The mass ratio of the first sintered product to the carbon source II is 1:0.02~0.05; c. The conditions for the sand milling treatment II include: a rotation speed of 400-2500 rpm and a time of 2-6 hours; d. The drying process II includes spray drying II; optionally, the inlet air temperature of the spray drying II is 260-280℃ and the outlet air temperature is 90-110℃. e. The conditions for the sintering treatment II include: a temperature of 750~820℃ and a time of 5~10h; f. The particle size D50 of the slurry is 0.2-0.5 μm; g. The material after the sand milling treatment II includes large particles with a particle size D50 of 0.6-1.2μm and small particles with a particle size D50 of 0.2-0.4μm; based on the total mass of the material after the sand milling treatment II, the mass percentage of the large particles is 30-70wt%.

9. A lithium-ion battery, characterized in that, This includes lithium iron phosphate cathode materials as described in any one of claims 1-5 or lithium iron phosphate cathode materials prepared by the preparation method described in any one of claims 6-8.

10. An electrical-related device, characterized in that, Including the lithium-ion battery as described in claim 9.